A Novel and Practical Continuous Flow Chemical Synthesis of Cannabidiol (CBD) and its CBDV and CBDB Analogues. Issue 8 (1st February 2021) - Chiurchiù, Elena; Sampaolesi, Susanna; Allegrini, Pietro; Ciceri, Daniele; Ballini, Roberto; Palmieri, Alessandro
Abstract: Cannabidiol is one of the main non‐psychoactive cannabinoids present in Cannabis sativa and, in the last decade, it is gaining great interest among the scientific community for its pharmaceutical, nutraceutical, and cosmetic applications. Herein, we report the first continuous flow chemical synthesis of cannabidiol (CBD) and its analogues cannabidivarin (CBDV) and cannabidibutol (CBDB). This approach permits to synthesize products in very good yields (55–59 %), limiting the formation of psychoactive and illegal cannabinoids such as tetrahydrocannabinol (THC). Abstract : Flow chemical synthesis has been fruitfully used for synthesizing cannabidiol (CBD) and its analogues cannabidivarin (CBDV) and cannabidibutol (CBDB) in 55 %, 56 %, and 59 % yields respectively. This approach permitted both to synthesize products in very short reaction time (residence time 7 minutes) and minimized the formation of psychoactive and illegal cannabinoids such a tetrahydrocannabinol (THC).